New Shanghai Disneyland futuristic Tomorrowland built using Scott Bader's Crestapol® resin and Crystic® FR gelcoat. Issue 5 (September 2016) - Gray, Neil
Abstract : After breaking ground back in 2011, Disney and Shanghai Shendi Group officially opened the spectacular new Shanghai Disneyland resort on 16th June 2016. This latest resort in China has six themed lands including 'Tomorrowland' featuring popular futuristic Disney characters including Tron, Lilo and Stich, and Toy Story's Buzz Lightyear. Extensive sections of both the interior and exterior of the buildings and show-sets in Tomorrowland, covering a total area of over 2300 m 2, were constructed from fire retardant (FR) gelcoated composite molded parts in several hundred different complex shaped and sized components.